Exploring the driving forces of CO2 emission changes in Chinese cities: A production-theoretical decomposition analysis - Cao, Ruili; Zhao, Zhibo (Frontiers in Environmental Science, 2022)
Analyzing the forces driving CO2 emissions in cities could provide valuable information for carbon reduction policies in China. This study uses an improved production-theoretical decomposition analysis to evaluate the CO2 emissions of 282 cities in China during 2003–2017. The empirical results show that the scale, energy intensity, and desirable output productivity effects contributed to about 15.03%, 3.64%, and 2.3% growths in CO2 emissions on average, respectively, while the potential CO2 emission and undesirable output productivity effects were responsible for 5.81% and 5.72% reductions in CO2 emissions. By classifying the sample cities and analyzing them further, it was found that the potential CO2 emission effect has a stronger inhibitory impact in resource-based cities. However, the promoting effects of the scale effect is more obvious in non-resource-based cities. From a spatial distribution perspective, the potential CO2 emission effect has a more obvious inhibitory role, and the energy intensity effect is a strong measure for controlling the growth of CO2 emissions in the eastern region. However, the contribution of the scale effect to CO2 emissions is more pronounced in the western region. In addition, we found that the desirable output productivity effects had a suppressive effect in the eastern region and facilitating effects in the central and western regions. The undesirable output productivity effect had a suppressive effect on the growth of CO2 emissions in all three regions, but the suppressive effects were more pronounced in the eastern region.